On the Origin of the Above-Room-Temperature Magnetism in the 2D van der Waals Ferromagnet Fe3GaTe2 - Ruiz, Alberto M.; Esteras, Dorye L.; López-Alcalá, Diego; Baldoví, José J. (Nano letters, 2024)
2D magnetic materials have attracted growing interest driven by their unique properties and potential applications. However, the scarcity of systems exhibiting magnetism at room temperature has limited their practical implementation into functional devices. Here we focus on the van der Waals ferromagnet Fe3GaTe2, which exhibits above-room-temperature magnetism (T c = 350–380 K) and strong perpendicular anisotropy. Through first-principles calculations, we examine the magnetic properties of Fe3GaTe2 and compare them with those of Fe3GeTe2. Our calculations unveil the microscopic mechanisms governing their magnetic behavior, emphasizing the pivotal role of ferromagnetic in-plane couplings in the stabilization of the elevated T c in Fe3GaTe2. Additionally, we predict the stability, substantial perpendicular anisotropy, and high T c of the single-layer Fe3GaTe2. We also demonstrate the potential of strain engineering and electrostatic doping to modulate its magnetic properties. Our results incentivize the isolation of the monolayer and pave the way for the future optimization of Fe3GaTe2 in magnetic and spintronic nanodevices.